5th AIAA/CEAS Aeroacoustics Conference and Exhibit 1999
DOI: 10.2514/6.1999-1847
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic noise reducing techniques by using pile-fabrics

Abstract: Aerodynamic noise radiated from bodies in subsonic flow is caused by the generation, acceleration and interaction of vortices. Therefore, in order to reduce the aerodynamic noise, we need skillful turbulence management or control. In other words, it is most important to alleviate such vertical motions.In this paper, we examine noise reducing effects of pile-fabrics, namely cloth materials with fine and high density fibers like fur or down, that are used to cover the body surface. Simple tests show that pile-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 0 publications
4
14
0
Order By: Relevance
“…Apart from the described increases in flow noise, the fur is responsible for the complete suppression of the first and second harmonics of the aeolian tone. This is in good agreement with the results of Nishimura et al [16], who performed measurements on cylinders covered by pile fabrics and found a noticeable decrease of the vortex shedding peak. The aft body modification also helps with suppressing the harmonics of the vortex shedding noise.…”
Section: Results Of the Acoustic Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…Apart from the described increases in flow noise, the fur is responsible for the complete suppression of the first and second harmonics of the aeolian tone. This is in good agreement with the results of Nishimura et al [16], who performed measurements on cylinders covered by pile fabrics and found a noticeable decrease of the vortex shedding peak. The aft body modification also helps with suppressing the harmonics of the vortex shedding noise.…”
Section: Results Of the Acoustic Measurementssupporting
confidence: 93%
“…In general, solid structures covered with hairs or fibres, such as fluffy bodies, are known to affect the generation of flow induced noise [16,17]. The present investigation intends to describe the consequence of the presence of hairy flaps on the noise generated by cylinders in a flow, especially regarding the spectral modification and possible acoustic damping impact of such flaps.…”
Section: Introductionmentioning
confidence: 99%
“…Although the modification of structural shapes is effective in reducing aerodynamic noise, such measures are limited to a certain extent due to the various functions that must be maintained. The reduction of such noise has been achieved by covering the surface of objects with fur materials [4], [5] -a technique based on the reduction of vorticity. However, it is difficult with the application of fur materials to satisfy the requirements of durability against weathering in railway vehicles.…”
mentioning
confidence: 99%
“…In the system, ambient air is taken in as an entrainment flow, and the surplus flow is released to the ambient air through an outlet. The pile-fabric material is a furlike material with fine fibers of about 10mm long applied on the inner surface of the collector to reduce aerodynamic noise (10)(11). The acoustic opening is an original countermeasure developed in this investigation.…”
Section: Results Of Investigationmentioning
confidence: 99%
“…For example, the diffuser duct downstream of the fan was reshaped with a cross-section area that increased more gradually than that in the original duct. Furthermore, the entrainment system (10) was applied to smooth the flow conducted by the collector, and a pile-fabric material (10)(11) was set on the inner surface of the collector to reduce the pressure fluctuations.…”
Section: Swaying Componentmentioning
confidence: 99%